2008
DOI: 10.1080/15563650701586397
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of self-reported use of amphetamine, barbiturates, benzodiazepines, cannabinoids, cocaine, methadone, and opiates among acutely hospitalized elderly medical patients

Abstract: Among 100 randomly selected mainly elderly medical patients, undeclared use of illicit drugs was rare. However, some patients underreported use of benzodiazepines and cannabinoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Furthermore, self report and objective indices of drug use in previous studies have shown strong associations, indicating self-report drug use to be reliable (e.g. Glintborg et al, 2008;Basurto et al, 2009). Despite the reliability of self-report data there still remains the issue concerning the purity of cocaine that has been consumed in these users.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, self report and objective indices of drug use in previous studies have shown strong associations, indicating self-report drug use to be reliable (e.g. Glintborg et al, 2008;Basurto et al, 2009). Despite the reliability of self-report data there still remains the issue concerning the purity of cocaine that has been consumed in these users.…”
Section: Discussionmentioning
confidence: 87%
“…However, self report and objective indices of drug use in previous studies have shown strong associations (e.g. Glintborg et al, 2008;Basurto et al, 2009). Nevertheless, it is possible that constituents other than cocaine may have contributed to the observed effect.…”
Section: Discussionmentioning
confidence: 93%
“…A study of medicinal drug use among Danish elderly people also found that the distribution of drug consumption resembled a log-linear shape (Barat, Andreasen, & Damsgaard, 2000). Another Danish study (Glintborg, Olsen, Poulsen, Linnet, & Dalhoff, 2008) demonstrated, however, that even patients' self-reports of medicinal drug use is fairly inaccurate and often under-reported when compared to prescription records. The present study adds to the literature not only by demonstrating a similar highly skewed distribution of a prescription drug based on a more reliable and accurate measure but also showing a significant positive association between overall sales and prevalence of excessive use or misuse of the drug.…”
Section: Discussionmentioning
confidence: 93%